Network programming in .NET : with C♯ and Visual Basic .NET - Reid, Fiach (Elsevier/Digital Press, 2004)
The purpose of this book is to provide tools to design and implement network-orientated applications in .NET. It is also a guide for software designers to choose the best and most efficient way to implement mission critical solutions. The book addresses real-world issues facing professional developers, such as using third-party components as opposed in-house development. It differentiates itself from existing .NET publications because it is aimed at experienced professionals and concentrates on practical, ready-to-use information. The book is written in two languages C♯ and VB.NET, and covers never-before published information on Telephony in .NET and packet-level networking. This is the second book in the Digital Press Software Development Series. Coverage of lower level protocols allows implementation of performance-centric applications Demonstrates the feasibility of developing telephony solutions in-house rather than outsourcing Written in VB.NET and C♯ to assist readers working in either language Coverage of Email, FTP and the WWW allows implementation of applications in all three areas.